(untitled) (Atti del Sodalizio Glottologico Milanese, 2021)
On the phonological status of Rigvedic tonal sandhi. The rules governing the distribution of tones in the language of the R̥gveda can be philologically reconstructed on the basis of three main kinds of sources: Old Indic treatises, diacritics employed in the manuscript tradition, and modern styles of R̥gveda recitation. This reconstructed tonal system can be analysed in the light of the universals of tone rules identified in the last decades by studies in phonological theory. The language of the R̥gveda turns out to be a system that has two underlying and three surfacing tone levels and is characterised by a typologically noteworthy – albeit not unnatural – phenomenon of unbounded High Tone Spread. The possibility is not ruled out that some of the properties of the R̥gvedic tonal grammar were specific to a ritual/recitational register of language.